Wind Turbine Level Energy Storage for Low Voltage Ride Through (LVRT) Support - (:unkn) unknown (My University, 2012)
Renewable energy is a green source of energy that is clean, available and sustainable. Wind energy generation has been experiencing the largest growth among renewable sources due to lower cost and advanced technologies. Wind energy power plants or farms need low maintenance and last for a long time. The increasing higher penetration of wind energy in the grid has transformed wind energy into major player in grid operation and economics. Wind energy systems now have to participate in grid support and provide ancillary services. Variable wind speed leads to variable wind power generation, voltage fluctuations, and frequency deviations, which are the main problems related to wind energy integration into a grid. These problems become more evident in weak grids. In addition, wind farms have to take the grid problems into consideration and have to provide support during grid instability and transients. In this thesis, a PMSG wind turbine full energy conversion system design and modeling have been performed using Matlab Simulink. The system is grid integrated and applies MPPT control to extract the maximum power from the wind and utilizes full conversion circuitry to interface the unregulated generator AC power to the grid. Modules of Lithium-Ion Capacitors (LIC) have been placed on the DC bus in order to support the grid with wind energy power smoothing and LVRT. LICs offer high power density and reasonable energy density. During grid faults, wind energy can be stored in the LICs and discharged into the grid as soon as the voltage is restored. This feature will support the grid to stabilize the voltage. Detailed modeling of the architecture and controls has been performed to verify the viability of the proposed system.
Keywords: Back to Back Converter Control; Low Voltage Ride Through; Lvrt; Wind Turbine Modeling